Diaphragmatic hernia into the pericardium: case report - Esparza-Lara, Fernando Alvaro; Quiroga-Garza, Alejandro; Guzman-Lopez, Santos (International Surgery Journal, 2018)
Laparoscopic approach for diaphragmatic hernias has proven to be superior to open surgery, however debate between thoracoscopy versus transperineal laparoscopy continues. Author report the case of a 66 years old man with a rare congenital larrey hernia that protrudes into the pericardium. Abdominal laparoscopic surgery was performed with successful reduction of content and repair of defect, placing a composite mesh and drain. Follow-up was uneventful. The review of literature revealed this as a rare atraumatic peritoneal-pericardium hernia. Author demonstrate an abdominal laparoscopic approach as a safe and adequate technique in such case.